EDUKASI DAMPAK SEKS BEBAS DAN PENYALAHGUNAAN NAPZA TERHADAP KESEHATAN REPRODUKSI REMAJA - Lailiyana Lailiyana; Fathul Jannah; Yan Sartika (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2023)
Today's youth are faced with an environment where everything changes very quickly. Along with thedevelopment of science, especially in the field of information technology with all the facilities to get information incyberspace, it is very open and films shown by various electronic media tend to highlight sexual behaviors that can displayadolescent behavior towards free sex. Drug abuse is also a youth problem that cannot be resolved. Narcotics, psychotropicsand addictive substances (NAPZA) which are consumed by teenagers continuously without indications and supervision inexcessive amounts to the point where dependence occurs and cause various impacts/problems on the body including thereproductive organs of adolescents. The purpose of this community service activity is to increase youth's knowledge andunderstanding of the impact of free sex and the threat of drugs on adolescent reproductive health. The method of activitycarried out is to provide education to adolescents in the form of counseling about the impact of sex-free and drug-taking onadolescent reproductive health. Educational activities in the form of counseling were carried out for 1 day on February 252023 in the Riau Province Plus High School Hall attended by 107 students of class X and XI. The material presented wasabout Adolescent Reproductive Health, Free Sex, Narcotics and Addictive Substances. Activity evaluation was carried outby giving pretest and posttest questionnaires. The results of the activity showed that there was an increase in theknowledge and understanding of adolescents before and after being given education, namely from an average score of 55during the pretest to an average score of 85 during the posttest. It is very important for adolescents to be given regulareducation about the impact of free sex and the threat of drugs on adolescent reproductive health so that they can preventfree sex behavior and eradicate drugs.Keywords: Teenager, education, free sex, drug abuse, reproductive health.